2015
DOI: 10.1038/mt.2014.232
|View full text |Cite
|
Sign up to set email alerts
|

Sourcing of an Alternative Pericyte-Like Cell Type from Peripheral Blood in Clinically Relevant Numbers for Therapeutic Angiogenic Applications

Abstract: Autologous cells hold great potential for personalized cell therapy, reducing immunological and risk of infections. However, low cell counts at harvest with subsequently long expansion times with associated cell function loss currently impede the advancement of autologous cell therapy approaches. Here, we aimed to source clinically relevant numbers of proangiogenic cells from an easy accessible cell source, namely peripheral blood. Using macromolecular crowding (MMC) as a biotechnological platform, we derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…249, 259 A recent study found that injection of blood-derived pericyte-like cells could rescue affected tissue by accelerating angiogenesis in a model of hind limb ischemia. 265 This result indicates that transplantation of pericyte progenitor cells may be a promising therapy for ischemia and could be possibly applied in ischemic stroke. More intriguingly, pericytes isolated from the ischemic regions of mouse or human brains reveal mesenchymal multi-lineage developmental properties when cultured under oxygen/glucose depriving environment, and could differentiate into both neural and vascular lineage cells.…”
Section: Part II Neurovascular Injury and Repair After Ischemic Strokementioning
confidence: 90%
“…249, 259 A recent study found that injection of blood-derived pericyte-like cells could rescue affected tissue by accelerating angiogenesis in a model of hind limb ischemia. 265 This result indicates that transplantation of pericyte progenitor cells may be a promising therapy for ischemia and could be possibly applied in ischemic stroke. More intriguingly, pericytes isolated from the ischemic regions of mouse or human brains reveal mesenchymal multi-lineage developmental properties when cultured under oxygen/glucose depriving environment, and could differentiate into both neural and vascular lineage cells.…”
Section: Part II Neurovascular Injury and Repair After Ischemic Strokementioning
confidence: 90%
“…In addition, they lacked MSCs markers such as CD146, thus were distinguishable from mesenchymal pericytes and expressed many angiogenic markers, such as VEGFR-1 and VEGFR-2. Although these cells had a monocytic origin, they exhibited a stable phenotype, as they could not be polarized towards M1 or M2 macrophages, nor did they exhibit macrophage features such as the ability to phagocytose [74]. Thus, although they were monocyte derived, they did not resemble macrophages.…”
Section: Sourcing Hematopoietic Pericytes From Peripheral Bloodmentioning
confidence: 95%
“…Two years prior to this we published a study that described the isolation of a cell population from human adult peripheral blood closely resembling hematopoietic pericytes. Peripheral blood mononuclear cells (PBMCs) were cultured as a crude mixture under mixed macromolecular crowding (MMC) [74]. The crowded conditions that are normally found in vivo are emulated in vitro by the addition of polysucrose molecules [75,76].…”
Section: Sourcing Hematopoietic Pericytes From Peripheral Bloodmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the major aims in regenerative medicine is to engineer biomaterials that can be readily transplanted to replace or to induce the regeneration of damaged tissues with the aim to resume the original function . For this purpose, biomaterials such as hydrogels are supplemented with progenitor cells that have a regenerative potential to form tissue in vitro or upon transplantation. Natural materials such as gelatin‐based hydrogels represent promising candidates for cellular carriers because of their tissue‐related biochemical, biophysical and biomechanical properties .…”
Section: Introductionmentioning
confidence: 99%